O tom e o som: diálogos entre a ciência e a música - Adalberto, Paulo Roberto (Universidade Federal de São Carlos, 2024)
The relationships between musical and scientific languages are historically well established, and in the global understanding of the sound phenomenon, the connections between science and music stand out. Musicology constitutes a scientific field in itself that generates and unifies science. The tuning of scales, the production of sound and its properties, the sensitivity and rationalization of sound mobilize knowledge, skills, attitudes, and values from different areas and provoke scientific, historical, social, and aesthetic discussions. By facilitating access to concepts that are sometimes overly abstract from various orders, as well as through its psychological effects, musical practice (from composition to appreciation) presents itself as an interesting tool in teaching. Such discussion has led to the proposal of workshops for building musical instruments, organized into four modules, as presented here. In addition to providing low-cost teaching material, the workshops propose didactic activities for science education, mediated by self- uided musical experiences during the construction of instruments with defined tuning. The playful, cognitive, and affective aspects with which music touches the individual can generate reflections and pedagogical decisions by teachers from different perspectives. Transversality and multidisciplinarity, promoting nterpersonal skills for the comprehensive systematization of evolving knowledge, underpin the proposal. The manifestations of Brazilian culture are also emphasized during the workshops.

Les relations entre les langages musical et scientifique sont historiquement bien établies, et dans la compréhension globale du phénomène sonore, les connexions entre la science et la musique se démarquent. La musicologie constitue un champ scientifique en soi qui génère et unifie la science. L’accordage des échelles, la production du son et ses propriétés, la sensibilité et la rationalisation du son mobilisent des connaissances, des compétences, des attitudes et des valeurs de différents domaines et suscitent des discussions scientifiques, historiques, sociales et esthétiques. En facilitant l'accès à des concepts parfois trop abstraits de divers ordres, ainsi que par ses effets psychologiques, la pratique musicale (de la composition à l'appréciation) se présente comme un outil intéressant dans le domaine de l'enseignement. Une telle discussion a donné lieu à la proposition d'ateliers de construction d'instruments de musique, organisés en quatre modules, présentés ici. En plus de fournir du matériel pédagogique à faible coût, les ateliers proposent des activités didactiques d'éducation aux sciences, médiées par des expériences musicales autoguidées, lors de la construction d'instruments avec un accordage défini. Les aspects ludiques, cognitifs et affectifs avec lesquels la musique touche l'individu peuvent générer des réflexions et des décisions pédagogiques de la part des enseignants sous différentes perspectives. La transversalité et la multidisciplinarité, qui favorisent les compétences interpersonnelles de systématisation intégrale des connaissances en évolution, soutiennent la proposition. Les manifestations de la culture brésilienne sont également soulignées pendant les ateliers.

Las relaciones entre los lenguajes musical y científico están históricamente bien establecidas, y en la comprensión global del fenómeno sonoro destacan las conexiones entre la ciencia y la música. La musicología constituye un campo científico en sí mismo que genera y unifica la ciencia. El afinamiento de escalas, la producción del sonido y sus propiedades, la sensibilidad y la racionalización del sonido movilizan conocimientos, habilidades, actitudes y valores de diferentes áreas y suscitan discusiones científicas, históricas, sociales y estéticas. Al facilitar el acceso a conceptos que a veces son demasiado abstractos de diversos órdenes, así como por sus efectos psicológicos, la práctica musical (desde la composición hasta la apreciación) se presenta como una herramienta interesante en la enseñanza. Tal discusión ha dado lugar a la propuesta de talleres de construcción de instrumentos musicales, organizados en 4 módulos, que se presentan aquí. Además de proporcionar material didáctico de bajo costo, los talleres proponen actividades didácticas de educación para las ciencias, mediadas por experiencias musicales autoguiadas, durante la construcción de instrumentos con afinación definida. Los aspectos lúdicos, cognitivos y afectivos con los que la música toca al individuo pueden generar reflexiones y decisiones pedagógicas por parte de los profesores desde diferentes perspectivas. La transversalidad y la multidisciplinariedad, promotoras de las habilidades interpersonales de sistematización integral del conocimiento en evolución, sustentan la propuesta. Las manifestaciones de la cultura brasileña también se enfatizan durante los talleres.
The tone and the sound: dialogues between science and music
Keywords: Música e ciência; Construção de instrumentos musicais; Temperamento de escalas; Som físico, fisiológico e musical; Ecologia sonora; Vivência musical; Music and science; Construction of musical instruments; Temperament of scales; Physical, physiological, and musical sound; Sound ecology; Musical experience; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM; LINGUISTICA, LETRAS E ARTES::ARTES::MUSICA::INSTRUMENTACAO MUSICAL